The contribution of leisure and entertainment to the evolving polycentric urban network on regional scale - towards a new research agenda - Arie Romein (European Regional Science Association (ERSA), 2005)
The urban landscape in advanced economies transforms from monocentric cities to polycentric urban networks on regional scale. The growing amount of research that is being devoted to this transformation sticks to classic activity systems like residential development, economic production and employment and commuting. Synchronous to this transformation, a 'new' activity system, outdoor leisure and entertainment, increasingly leaves its stamp on the economic performance and spatial organisation of urban areas in general. Due to tremendous dynamics of consumption, production, and urban politics with regard to this activity system, it is subject of a composite of spatial pressures for centralisation in inner-cites, de-concentration away form central cities and (re-)concentration in suburbs and exurban places. Notwithstanding this composite spatial dynamics, leisure and entertainment are not part of the research agenda on regional polycentric urban networks. Based on brief overviews of literature on both polycentric urban development and the dynamics of leisure and entertainment in urban areas, this paper presents a few basic research questions in order to initiate the research agenda on the contribution of the leisure activity system to the development of polycentric urban networks on regional scale.
Keywords: 330